Hamlet, or about Death: A Romanian Hamlet directed by Vlad Mugur (2001) - Matei-Chesnoiu, Monica (Multicultural Shakespeare: Translation, Appropriation and Performance, 2019)
This essay looks at the 2001 Romanian production of Hamlet directed by Vlad Mugur at the Cluj National Theatre (Romania) from the perspective of geocriticism and spatial literary studies, analysing the stage space opened in front of the audiences. While the bare stage suggests asceticism and alienation, the production distances the twenty-first century audiences from what might have seemed difficult to understand from their postmodern perspectives. The production abbreviates the topic to its bare essence, just as a map condenses space, in the form of “literary cartography” (Tally 20). There is no room in this production for baroque ornaments and theatrical flourishing; instead, the production explores the exposed depth of human existence. The production is an exploration of theatre and art, of what dramatists and directors can do with artful language, of the theatre as an exploration of human experience and potential. It is about the human condition and the artist’s place in the world, about old and new, about life and death, while everything happens on the edge of nothingness. The director’s own death before the opening night of the production ties Shakespeare’s Hamlet with existential issues in an even deeper way than the play itself allows us to expose.